Grasping the Democratic Peace : Principles for a Post-Cold War World - Russett, Bruce M. (Book collections on Project MUSE., 1995)
Is Communism's collapse merely the passing of a particularly lethal adversarial relationship between the super powers - or an extraordinary chance to make fundamental changes in how nations resolve conflicts? In answering this query, Bruce Russett shows that the world's great nations now have an opportunity to realize the "democratic peace" envisioned by Immanuel Kant and Woodrow Wilson. These two men suggested in their own eras what has become increasingly clear in our own: democracies do not fight each other. Now, as the Clinton administration strives to replace the goals of the Cold War with a "pro-democracy" foreign policy, the desire for a shared peace among democracies is becoming one of the most urgent concerns not only of the United States but of the entire international community. In this original and far-reaching study of the relevant issues, Russett discusses instances of "democratic peace" from preindustrial societies through ancient Greece through the modern international system of the nineteenth and twentieth centuries. His account reveals that the relative peace between democracies is due not to their wealth, their alliances, and their distance from each other, but to the norms and strategies characteristic of democracy-to-democracy relationships. By illuminating the conflict-resolving mechanisms inherent in these relationships, he explains one of the most promising developments of the modern international system: the striking fact that the democracies that it comprises have almost never fought each other. This profound work not only addresses a broad audience of scholars and policy professionals but also reaches outside the professional debate to engage other readers who are also seriously interested in the new administration's foreign policy and in international relations are generally. It promises to become the major text of the continuing dialogue on whether and how a "democratic peace" may finally be achieved